Review of Islamic Law on Keeping Pets That Defile Neighbors' Houses and Eat at Neighbors' Houses - Musaddiq, M Azhar; Hafidzi, Anwar (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This research examines the habits of pets owned by neighbors who often disturb and dirty neighbors' houses and also sometimes eat food belonging to neighbors without the knowledge or permission of the homeowners. The purpose of this research is to find out what is the law if keeping neighbors' pets often pollutes the neighbors' houses and sometimes eats the neighbor's food without the knowledge or permission of the home owner. What causes this problem to occur frequently in several residential areas. Even though everyone agrees that it is a disgraceful act to disturb other people's comfort and take what is not rightfully theirs, this research has differences from the legal approach to maintaining it. The research method used in this study is a field research method that often occurs at the researcher's house and around the researcher's house, namely the Pamukan Utara District of Kotabaru and is analyzed descriptively qualitatively, namely the discussion obtained by collecting data from interviews and sources of Islamic literature such as the Qur'an, hadith, and the opinion of the scholars regarding the problem of disturbing neighbors and eating something that does not belong to them. From the results of this study it can be concluded that keeping pets that pollute the neighbor's house and eating at the neighbor's house without the knowledge or without the permission of the owner of the house is illegal because it is a sin. This problem often arises in the community, and it is important for the community to know about the law in order to create harmony, Keywords : Raising Pets, Disturbing, Neighbor's House ABSTRAK Penelitian ini mengkaji mengenai kebiasaan binatang piaraan punya tetangga sekitar yang sering mengganggu dan mengotori rumah-rumah tetangga dan juga terkadang memakan makanan punya tetangga tanpa sepengetahuan atau tanpa seizin pemilik rumah. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana hukumnya jika memelihara binatang-binatang piaraan tetangga yang sering mengotori rumah-rumah tetangga dan terkadang memakan makanan punya tetangga tanpa sepengetahuan atau tanpa seizin pemilik rumah. Apa yang menyebabkan permasalahan ini sering terjadi di beberapa daerah pemukiman warga. Meskipun semua sepakat mengganggu kenyamanan orang lain dan mengambil yang bukan haknya adalah merupakan perbuatan tercela, tapi penelitian ini memiliki perbedaan dari pendekatan hukum memeliharanya. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian lapangan yang sering terjadi di rumah peneliti dan sekitaran rumah peneliti yaitu daerah Kecamatan Pamukan Utara Kotabaru dan dianalisis secara deskriptif kualitatif, yaitu pembahasan yang diperoleh dengan mengumpulkan data dari wawancara dan sumber kepustakaan Islam seperti Al-Qur’an, hadits, dan pendapat para ulama yang berkenaan dengan permasalahan mengganggu tetangga dan memakan sesuatu yang bukan hak miliknya. Dari hasil penelitian ini dapat disimpulkan bahwa memelihara binatang piaraan yang mengotori rumah tetangga dan makan dirumah tetangga tanpa sepengetahuan atau tanpa seizin pemilik rumah hukumnya adalah haram karena itu perbuatan dosa. Permasalahan ini sering muncul di lingkungan masyarakat, dan masyarakat penting mengetahui terkait bagaimana hukumnya agar terciptanya kerukunan, kenyamanan, dan ketenangan dalam bertetangga. Kata Kunci : Memelihara Binatang Piaraan, Mengganggu, Rumah Tetangga